Practice-based holistic STEM teaching in VET - Henrik Hersom; Felicia Lind Benthien (Scandinavian Journal of Vocations in Development)
This article examines the significance of practice-based holistic STEM teaching in vocational education and training and how it can enhance students' motivation and learning in STEM subjects. The study shows that STEM teaching, which incorporates vocational practice, can motivate and include more student groups, including those with negative experiences from previous schooling. The article distinguishes between 'imagined vocational practice' and 'experienced vocational practice'. The article argues that the latter, which involves concrete, physical experiences, has the potential to strengthen students' motivation and increase the opportunities for participation in STEM teaching.